Contamination of surface and underground waters by nitrogen in South-West of Romania - Carciu Gheorghe (Review on agriculture and rural development, 2013)
Research was carried out in two localities in South-Western Romania, Latunas and Clopodia. The main goal of this research was to study the impact of rainfall in 2009 on nitrate, nitrite and ammonium accumulation in surface and underground waters in Latunas in June. There was the largest amount of nitrate, 209 mg/L because of the large amount of rainfall (111.6 mm). The high values of nitrate in October (115 mg/L), November (120 mg/L) and December (154 mg/L) was caused mainly by rainfall, more than the multiannual mean. In Clopodia, in May-August 2009, nitrite and ammonium content values were below maximum admitted limit (0/50 mg/L) both in the water samples from drilling and in the water samples from wells, except for the water samples from wells in June 2009 – 2.44 mg/L (Latunas) and 0.72 mg/L (Clopodia). This accumulation was caused mainly by the rainfall above the multiannual mean – 118.6 mm in June 2009.